Nilai-Nilai Religius dalam Novel Kembara Rindu Karya Habiburrahman El Shirazy Dan Relevansinya dengan Pembelajaran Sastra di SMA - Santosa Santosa; Kamarudin Kamarudin; Akhyarudin Akhyarudin (Universitas Batanghari Jambi, 2023)
The purpose of this study is to describe the religious values contained in the novel Kembara Rindu by Habiburahman El Shirazy. A novel with the theme of the virtues of studying, which is combined with the complexity of the daily struggles of a student of knowledge. This research is classified as descriptive research with a qualitative approach as a research procedure that produces descriptive data in the form of written or spoken words from people and observable behavior. The research instrument used was the researcher himself. The validity of the data is in the form of intrarater validity, namely by reading and reviewing the research subject repeatedly to obtain consistent and interater data, namely checking by discussing the results of observations with colleagues who have conducted research on moral values in literary works. The results of the analysis of this study indicate that the form of religious values contained in the novel Kembara Rindu. Includes the value of worship, the value of the spirit of jihad, morals and discipline, trust and sincerity